Managing start-ups for success: entrepreneurship in difficult times - Baisya, Rajat K. (London and New York: Routledge, 2022)
'World economics and the industrial environment recently has created a fertile ground for the creation of new enterprises and start-ups. This book skilfully identifies the challenges of building a new business venture from an idea to a marketable product. It highlights robust methods for keeping up with innovation; designing new ways to grow, improve, and market your product; and managing the changes in the business environment, market dynamics and other uncertainties The volume is rich with examples and case studies of many small and large businesses, it further reflects on the business and entrepreneurship ecosystem, the challenges and opportunities in India, entrepreneurship and women, e-commerce, the new generation of entrepreneurs, and exit strategies for entrepreneurs. An essential guide for entrepreneurs, professionals working in business management and marketing communications as well as scholars of business administration and financial sciences, this book by an industry expert offers many new and practiced approaches, examples, and lessons for innovative thinking and breaking new ground in business'--
Includes bibliographical references and index.
Keywords: New business enterprises; Entrepreneurship; Success in business